Remanescências do Império português em África - Brandão, José Manuel (2022)
This paper revisits the geological collection assembled by Portuguese Navy officers Hermenegildo Capelo and Roberto Ivens, during the famous Africa crossing (1884-85) “From Angola to the opposite coast”. Deposited at the museum of the Geological Survey in Lisbon, upon the return of travellers, the samples were classified by Nery Delgado and Alfredo Bensaúde. In the 1990s, the museum's African collections were transferred to the LNEG – Alfragide core library (Litoteca), where they were the object of a reconditioning and inventory, recently reviewed. In addition to their value as testimony to the scientific explorations undertaken by the Portuguese travellers in Africa, these samples, interpreted together with the homonymous text signed by the two explorers, illustrate many of the different lithologies crossed, from the African craton and to sedimentary borders.